Beyond Grades - Predicting Programme Learning Outcomes with Multi-Output Regression in Malaysian Higher Education - Muhammad Noorazizi Abd Ghani; Istas Fahrurrazi Nusyirwan (Universiti Sains Islam Malaysia, 2025)
Sains Insani, Volume 10 Issue 2 Page (124–138)